Endometrial Progesterone and Estrogen Receptors in Relation to Hormonal Levels in Women with Unexplained Recurrent Miscarriage - Gomaa, Ihab Adel; Sabry, Ahmed; Allam, Ihab Serag El-Din; Ashoush, Sherif; Reda, Ahmed (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective Recurrent miscarriage has been linked to hormonal disturbance due to dysregulation of its receptors rather than to the availability of the hormone. We aimed to investigate endometrial expression of progesterone and estrogen receptors in relation to serum and endometrial hormonal levels in unexplained recurrent miscarriage.Methods The present case control study included 20 cases with unexplained recurrent miscarriage and 20 parous women as controls. Ovulation was confirmed using an ovulation kit and 10 to 12 days after detecting the urinary luteinizing hormone surge, all women were subjected to a blood sample and to an endometrial biopsy. Progesterone and estrogen levels were measured in serum and in endometrial tissue and receptor concentrations were in the endometrial sample.Results Women with recurrent miscarriage showed significantly lower concentration of receptors in both the cytoplasm and the nucleus of endometrial tissue compared with controls. The nuclear/cytoplasm ratio of progesterone receptor was significantly higher in cases compared with controls, implicating that recurrent miscarriage is probably linked to nongenomic activity of the hormone; this was also significant for estrogen receptor. Serum progesterone and estrogen hormonal levels were comparable between groups while both hormones were significantly reduced in the endometrium of recurrent miscarriage cases. Receptors significantly correlated with endometrial hormonal level but not to serum level.Conclusion Recurrent miscarriage might be linked to reduced endometrial progesterone and estrogen receptors and appears to be more related to nongenomic activity of progesterone. Endometrial receptors expression correlates to tissue hormonal level rather than to serum hormonal level.
Keywords: Pregnancy loss; Receptor; Recurrent miscarriage; Estrogen; Progesterone